Laughing fit to kill : black humor in the fictions of slavery - Carpio, Glenda (Oxford ; New York : Oxford University Press, 2008)
Introduction. 1. "Laffin fit ter kill:" Black Humor in the Fiction of William Wells Brown and Charles W. Chesnutt. 2. The Conjurer Recoils: Slavery in Richard Pryor and Chappelle's Show. 3. Conjuring the Mysteries of Slavery: Voodoo, Fetishism, and Stereotype in Ishmael Reed's Flight to Canada. 4. "A Comedy of the Grotesque": Robert Colescott, Kara Walker and the Iconography of Slavery. 5. The Tragicomedy of Slavery in Suzan-Lori Parks' Early Plays. Notes. Bibliography. Index
Introduction; 1 "Laffin' fit ter kill": Black Humor in the Fiction of William Wells Brown and Charles W. Chesnutt; 2 The Conjurer Recoils: Slavery in Richard Pryor's Performances and Chappelle's Show; 3 Conjuring the Mysteries of Slavery: Voodoo, Fetishism, and Stereotype in Ishmael Reed's Flight to Canada; 4 "A Comedy of the Grotesque": Robert Colescott, Kara Walker, and the Iconography of Slavery; 5 The Tragicomedy of Slavery in Suzan-Lori Parks's Early Plays; Notes; Bibliography; Index.
Includes bibliographical references (pages 233-279) and index.
Print version record.
English.
eBooks on EBSCOhost
Keywords: American literature -- African American authors -- History and criticism; African American wit and humor -- History and criticism; Black humor; Slavery in literature; Comic, The, in literature; African Americans in literature; Humour noir américain -- Histoire et critique; Humour noir; Esclavage dans la littérature.; Comique dans la littérature.; Noirs américains dans la littérature.; HUMOR -- General; African American wit and humor; African Americans in literature; American literature -- African American authors; Black humor; Comic, The, in literature; Slavery in literature; Criticism, interpretation, etc